The Effect of The Fluctuations of Coal Price, BI Rate and Oil Price Upon The Total Debt of PT. Adaro Energy - Arif Surahman; Mahnun Mas'adi; Widhi Wicaksono (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
Debt management if done carelessly, can cause the company to experience financial difficulties in the future. The higher the debt held by the company, the higher the principal and interest installments that must be paid. In October 2021 in China there was an energy crisis that resulted in at least 20 provinces experiencing electricity supply shortages. This is due to the disruption of coal supply, which is where 70% of China's electricity needs are powered by coal intake (Sorongan, 2021). This shortage of coal supply is good news for coal businesses in the country.This article try to investigate what factors that can influence the Total Debt of Pt. Adaro Energy. The results concluded that Coal price dan BI Rate has a significant influence towards the Total Debt of Pt. Adaro Energy with the sig value test scores below the 5% confidence level threshold.